HUBUNGAN ANTARA ATRIAL FIBRILASISIMTOMATIK DAN ASIMTOMATIK DENGAN KLASIFIKASI GAGAL JANTUNG MENURUT NEW YORK HEARTASSOCIATION (NYHA)DI RUANG TULIP RSUD DR. H. ABDUL MOELOEK PROPINSI LAMPUNG - Eka Yudha Chrisanto; Linawati Novikasari; Triyoso Triyoso (Malahayati Nursing Journal, 2019)
ABSTRACT: RELATIONSHIP BETWEEN ATRIAL FIBRILASISIMTOMATIC AND ASIMTOMATIC WITH CLASSIFICATION OF NEW YORK HEARTASSOCIATION (NYHA) HEART FAILURE IN TULIP ROOM RSUD DR. H. ABDUL MOELOEK PROVINSI LAMPUNG Background: Atrial fibrillation (atrial fibrillation, AF) is supraventricular tachycardia with uncoordinated characteristics of atrial activation. The incidence of AF is increasing especially with increasing life expectancy. AF management is still a problem. Until now, there have been two basic intervention choices: restore and maintain a sinus rhythm or control the heart rate.Purpose: To find out the relationship between symptomatic and asymptomatic atrial fibrillation and heart failure classification according to the New York Heart Association in the Tulip Room of the RSUD Dr. H. Abdul Moeloek Lampung Province in 2018Methods: The sampling technique used in this study used accidental sampling technique. The research institute uses a medical record. Data analysis using univariate (average) and bivariate (t test).Results: Most of the patients at the Tulip Room of the Regional General Hospital Dr. H. Abdul Moeloek Lampung Province in 2018 is a patient with New York Heart Association (NYHA) 2-4 heart failure, which is 33 people (89.2%). Most of them are in the Tulip Room of the Regional General Hospital Dr. H. Abdul Moeloek Lampung Province in 2018 is a patient with Atrial Fibrillation, which is as many as 30 people (81.1%). There is a relationship between symptomatic and asymptomatic atrial fibrillation with the classification of heart failure according to the New York Heart Association in the Tulip Room of the RSUD Dr. H. Abdul Moeloek Lampung Province in 2018 with p-value = 0.016 and OR = 2.046.Conclusion: There is a relationship between symptomatic and asymptomatic atrial fibrillation and the classification of heart failure according to the New York Heart Association in the Tulip Room of the RSUD Dr. H. Abdul Moeloek Lampung Province in 2018. Keywords: Atrial Fibrillation Symptomatic, Asymptomatic, Heart Failure